Eco-Friendly Cotton/Linen Fabric Treatment Using Aqueous Ozone and Ultraviolet Photolysis - Kengo Hamada (Catalysts, 2020)
Chemicals for the scouring and bleaching of fabrics have a high environmental load. In addition, in recent years, the high consumption of these products has become a problem in the manufacture of natural fabric products. Therefore, environmentally friendly, low-waste processes for fabric treatment are required. In this paper, we discuss the bleaching of fabrics using advanced oxidation processes (AOP). These processes use electrochemically generated aqueous ozone and ultraviolet (UV) irradiation to achieve bleaching. However, colour reversion often occurs. In this study, we suppressed unwanted colour reversion by treatment with rongalite. After treatment, changes in fabric colour were determined by measuring the colour difference and reflectance spectra. The best bleaching effect was obtained when ozone and UV irradiation treatments were combined, achieving results similar to those of a conventional bleaching method after 60 min of UV irradiation. In addition, the AOP treatment resulted in the simultaneous scouring of the fabric, as shown by the increased hydrophilicity of the fabric after AOP treatment. Thus, this AOP process represents a new fabric bleaching process that has an extremely low environmental impact.